Coenzyme Q10 modulates the immunity by enhancing mononuclear macrophage, NK cell activity, and regulating gut microbiota - Liang, Yajun; Han, Yang; Xiao, Ling; Su, Yupeng; Bao, Tongen; Ji, Xia; Jia, Longgang; Zhang, Jing (Frontiers in Nutrition, 2025)
IntroductionCoenzyme Q10 (CoQ10), an important fat-soluble, bioactive molecule that predominantly found in the inner mitochondrial membrane, is widely used in functional food and health food raw materials, which has garnered considerable attention due to its potential role in immunoregulation. However, the intrinsic mechanism of CoQ10 on immunity, and the relationship to the gut microbiota have not been elucidated.MethodsHere, we conducted a series of in vivo experiments with the aim of comprehensively exploring the effect of CoQ10 on both cellular and humoral immune functions, and on gut microbiota communities in mice.ResultsCoQ10 showed negligible impact on both mouse body weight fluctuations and tissue indices, but enhanced the mouse body immunity by elevating the carbon clearance ability and natural killer (NK) cellular viability. 16S rRNA gene sequencing revealed that administration of CoQ10 modulated the structure and composition of the gut microbiota in mice, notably by enhancing the abundance of Lactobacillus, Limosilactobacillus, and decreasing the abundance of Paramuribaculum species.DiscussionThis work makes a contribution to the application of CoQ10 as an immunomodulator in the biological, pharmaceutical and health care product industries.